‘‘We’re Working in the Dark Here’’: Education Needs of Teachers and School Staff Regarding Student Self-Injury - Berger, E.; Hasking, Penelope; Reupert, A. (Springer New York LLC, 2014)
Although teachers and other school staff encounter adolescents who self-injure, the behaviour evokes strong reactions. We (a) validated a measure of attitudes towards self-injury, (b) examined knowledge, confidence, and education needs regarding self-injury, and (c) explored the relationship between attitudes and responses to self-injury among 501 secondary school teachers and other school staff. Three factors reflecting participants’ attitudes were extracted. Experience was related to knowledge and confidence regarding self-injury, but not to attitudes. Thematic analysis of open-ended questions indicated a desire for education and resources. Implications for teacher education and school policies to support teachers in addressing self-injury are discussed.